ENRICHME: perception and interaction of an assistive robot for the elderly at home - Cosar, Serhan; Fernandez-Carmona, Manuel; Agrigoroaie, Roxana; Pages, Jordi; Ferland, Francois; Zhao, Feng; Yue, Shigang; Bellotto, Nicola; Tapus, Adriana (Springer, 2020)
Recent technological advances enabled modern robots to become part of our daily life. In particular, assistive robotics emerged as an exciting research topic that can provide solutions to improve the quality of life of elderly and vulnerable people. This paper introduces the robotic platform developed in the ENRICHME project, with particular focus on its innovative perception and interaction capabilities. The project’s main goal is to enrich the day-to-day experience of elderly people at home with technologies that enable health monitoring, complementary care, and social support. The paper presents several modules created to provide cognitive stimulation services for elderly users with mild cognitive impairments. The ENRICHME robot was tested in three pilot sites around Europe (Poland, Greece, and UK) and proven to be an effective assistant for the elderly at home.
Keywords: Robots autónomos; Ancianos - Asistencia a domicilio; Assistive robotics; Robot perception; Human–robot interaction